2014
DOI: 10.1021/jp506946b
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Understanding the Electrocatalytic Activity Enhancement by Superexchange Interaction toward OER in Alkaline Media of Ni–Fe LDH

Abstract: In the present work, the hydrotalcite-like materials known as layered double hydroxides (LDHs) were synthesized. The Ni–Al and Ni–Fe materials with different Ni/Fe ratio were obtained by coprecipitation method at variable pH. The LDH structure was verified by X-ray diffraction, Fourier transform infrared, and Raman spectroscopy. No secondary extra phases were observed for any material. The electronic properties were evaluated by UV–vis spectroscopy, while the magnetic ones were followed by electron paramagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
153
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(164 citation statements)
references
References 34 publications
11
153
0
Order By: Relevance
“…The calculated band gap of NiFe-CO 3 -LDH is 1.12 eV as shown in Figure S5. We found that different anion based solutions did not show an important catalytic effect on OER, which is in agreement with the experiment [42]. The valence band maxima were mainly as a result of the Fe 3d contribution, while the conduction band minima were mainly composed of the Ni 3d, Fe 3d and small O 2p orbitals.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The calculated band gap of NiFe-CO 3 -LDH is 1.12 eV as shown in Figure S5. We found that different anion based solutions did not show an important catalytic effect on OER, which is in agreement with the experiment [42]. The valence band maxima were mainly as a result of the Fe 3d contribution, while the conduction band minima were mainly composed of the Ni 3d, Fe 3d and small O 2p orbitals.…”
Section: Resultssupporting
confidence: 90%
“…In 2013, Dai and co-workers synthesized a carbon nanotubes/NiFe-LDHs complex [12], which was found to be highly active for the OER in alkaline solutions and exhibited higher electrocatalytic activity and stability for oxygen evolution than the commercially-available precious metal Ir catalysts. Guzmán-Vargas' group studied the electrocatalytic activity enhancement by superexchange interaction toward OER in an alkaline media of Ni-Fe LDH [42]. The arrangement of the Fe atoms in the lattice may form a specific magnetic structure that favors the superexchange interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the above comparison intuitionally reflects the spontaneous magnetism is a crucially decisive factor for the enhanced electrocatalytic performance of OER/ORR of Ni-Fe LDHs in alkaline media. The present result is not only consistent with the experimental observation [24] but also highlights the concept of magnetic catalysis, that is, only the regulation magnetic coupling is compatible with magnetic catalyst. It was proposed that the Fe atoms, rather than the Ni atoms, are the available sites for reactions in Ni-Fe LDHs [21].…”
Section: Resultssupporting
confidence: 91%
“…This again evidences that the Fe 3+ ions rather than the Ni 2+ ions in the LDHs are indeed the active sites, which agrees with the theoretical prediction based on the experiment [21]. And such, the impurity states, contributing to the magnetic coercivity for the nanosheet, instead of the VBM certainly will make a dominant effect on the successive oxidation-reduction reaction; and from another point of view, this verifies the fact that the real Ni2Fe LDHs are in general stable [23,24,31]. Crucially, the calculated adhesion energy of one Cl atom on the Ni2Fe hydroxide nanosheet is −2.70 eV, which is weaker than the dissociation energies of O-H (−5.29 eV per H atom) and Fe(Ni)-OH bonds (−3.02 eV Figure 5 Total and projected DOS and band structures of (a) Ni2Fe hydroxide, and (b) Ni2Fe(OH)6 nanosheets in the ground state, respectively.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation